The Impact of Prior Related Behavior on Stunting Incidents Abang I Health Center, Karangasem District, Bali, Indonesia - Kadek Dina Wulandari; I Ketut Gama; Komang Ayu Henny Achjar; I Wayan Suardana; I Gusti Ketut Gede Ngurah; Ketut Sudiantara (Health Dynamics, 2024)
Background: Stunting is growth failure in children under 5 years due to chronic malnutrition, often occurring during the first 1000 days of life. Maternal behavior during pregnancy has a major impact on fetal development and the possibility of stunting. This study aims to analyze the relationship between prior related behavior, such as blood increasing tablets consumption, antenatal care checks, and animal protein consumption, with the incidence of stunting in the Abang I Community Health Center Work Area, Karangasem Regency. Methods: Using non-probability sampling technique with Purposive sampling, with a total of 70 respondents from a total population of 230 people who met the inclusion criteria, namely mothers aged 15-45 years, mothers who had stunted toddlers and were registered in the Abang I Community Health Center Working Area. Results: Based on non-probability statistical tests. Spearman Rank parametric, found a significant p-value for blood increasing tablets consumption behavior (p=0.002), Antenatal care examination (p=0.004), and animal protein consumption (p=0.002), showing a value <0.05 which means there is a relationship with stunting incident. The majority of respondents showed bad behavior in these three areas, namely consump blood increasing tabletstion behavior 55.7%, antenatal care examination 55.7% and animal protein consumption 52.9%. It is hoped that health workers at the Community Health Center will follow up with pregnant women and teenage girls in coordination with the village or Community Health Center for education about the importance of blood increasing tablets, antenatal care examinations, and animal protein intake to prevent stunting in toddlers. Conclusion: There is a relationship between maternal behavior in consuming blood supplement tablets, antenatal care and animal protein consumption with the incidence of stunting in the working area of Puskesmas Abang I, Karangasem district, Bali, Indonesia.